2016
DOI: 10.1002/aqc.2641
|View full text |Cite
|
Sign up to set email alerts
|

Movement, depth distribution and survival of spinetail devilrays (Mobula japanica) tagged and released from purse‐seine catches in New Zealand

Abstract: 1. Mobulid rays are protected in New Zealand, but the spinetail devilray Mobula japanica is caught as bycatch in skipjack tuna purse seine fisheries.2. Between 2005 and 2014, rays were recorded in 8.2% of observed purse seine sets. Rays were caught during summer, with a 'hotspot' (24.3% of sets) near the shelf edge off North Island over seabed depths of 150-350 m. Rays were usually brailed aboard with the tuna catch from successful sets, but were often entangled in the bunt of the net during unsuccessful sets.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 27 publications
0
43
0
Order By: Relevance
“…Raw data are analyzed in-house by Wildlife Computers, who provide a report indicating pop-off date, location, daily values for temperature and depth, an indication of daily changes in light, and fate. Fate (i.e., the reason for tag release) is used to infer survivorship and is classified into one of four categories: (1) completed deployment, (2) sinker, a tag attached to a sinking animal that releases at 1700 m, (3) floater, a tag at the surface, and (4) sitter, a constant depth reading shallower than 1700 m. Completed deployment (category 1) indicates survival, sinker and sitter (categories 2 and 4) indicate mortality, and floater (category 3) could be interpreted as either survival or mortality, based on inspection of depth data [15].…”
Section: Methodsmentioning
confidence: 99%
“…Raw data are analyzed in-house by Wildlife Computers, who provide a report indicating pop-off date, location, daily values for temperature and depth, an indication of daily changes in light, and fate. Fate (i.e., the reason for tag release) is used to infer survivorship and is classified into one of four categories: (1) completed deployment, (2) sinker, a tag attached to a sinking animal that releases at 1700 m, (3) floater, a tag at the surface, and (4) sitter, a constant depth reading shallower than 1700 m. Completed deployment (category 1) indicates survival, sinker and sitter (categories 2 and 4) indicate mortality, and floater (category 3) could be interpreted as either survival or mortality, based on inspection of depth data [15].…”
Section: Methodsmentioning
confidence: 99%
“…A recent study carried out with electronic tags on the spine-tailed devil ray Mobula japanica in New Zealand waters showed that individuals reported to have swum vigorously when released died after two days (Francis and Jones, 2016). Thus, post-release behaviour might not necessarily be a good indicator of survival, or could be species-specific.…”
Section: Accepted Manuscriptmentioning
confidence: 97%
“…1). We selected these bounding boxes based on the expected distribution of mobulids in each region, which was supported by bycatch data from the eastern equatorial Pacific (Croll et al 2016), interviews with fishermen regarding capture locations in Sri Lanka, and records of long-distance movements in several Mobula species (Thorrold et al 2014, Francis & Jones 2017. We averaged chl a values over the entire bounding box for a given region and smoothed monthly averages into seasonal (3 mo) averages for plotting purposes.…”
Section: Environmental Datamentioning
confidence: 99%
“…The first possibility is that M. japanica is more piscivorous during the rainy season, and the landings and stomach content sampling during the dry season did not reflect the overall diet. While telemetry data suggest that M. japanica is restricted mainly to near-surface waters (Croll et al 2012), at least some individuals make regular dives to depths of 200 to 300 m (Francis & Jones 2017 (Heinrichs 2009), and it is possible that M. japanica engages in the same behavior in the Philippines. An alternative ex planation is that our trophic discrimination factors are incorrect, given the variability in published discrimination factors for elasmobranchs and the lack of experimentally derived discrimination factors for mobulids.…”
Section: Mixing Modelsmentioning
confidence: 99%
See 1 more Smart Citation